GAMBARAN PERTUMBUHAN DAN PERKEMBANGAN BALITA PEDAGANG PASAR DWIKORA PARLUASAN DI KOTA PEMATANG SIANTAR TAHUN 2012 - Romilly Purba (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Children  under  five years is as the  golden  period and as  good  time  to make optimal growth. The growth of  children  under  five  years of traditional  sellers in Dwikora Parluasan market was  frequently neglected because their parents  seldom  took  their  children to Integrated  Health Care  Unit. This research  is intended  to  describe the   growth and development of  the children in   Dwikora market  Pematang  Siantar  city in 2012.  This  was descriptive  research  using   cross sectional design.  Sample taken  was done with  purposive  sampling. The criteria was  with the  permission of the parents. The results of research showed  that  the growth of the children based on the  weight for height  index in Dwikora market Pematang  Siantar  city in 2012 was mostly normal. However, some  babies were  thin, very thin,  fat and  very fat. The growth based on the weight for age index,  mostly  were normal even though  some  with less  weight  and with problem in their growth. The growth based on the height for age and  weight for age  were mostly normal. However,  some children were short and very short.  The development of the  children in Dwikora market  was  good even though some  with problem  compared to other  normal children. Based on the results of research, it is suggested to health  providers to  give counseling  and guidance regarding the importance of  the  growth and development of the  children. The  availability of Integrated  Health Care  Unit is   expected in Dwikora market  such as what can  be found in  Horas market  Pematang Siantar. Key words :  Growth, Development, Children Under Five  Years of Traditional  Sellers